Mothers' status, food price shock and child nutrition in Karnataka - Debosree Banerjee; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2018)
Women's empowerment is increasingly put forth as a mean to promote child development. However, little empirical research has evaluated the pathways of women empowerment leading to it. This paper uses a household survey conducted in Karnataka, South India to explore the impact of female status on child anthropometric indicators aged below 11 years when food price shock occurs. We distinguish between exogenous status and endogenous status of women and argue that both are important to capture intrahousehold dimensions of women's empowerment. Endogenous status in our study is measured by mothers' work status and her time spent with children. Exogenous status is captured by a composite index constructed with parental educational gap, mother's age at marriage and years of marriage. Our finding suggests that endogenous status, measured by time reduces incidence of underweight, wasting and improves BMI significantly, but it is insignificant to affect weight for age scores. In the case of weight for age scores exogenous status becomes a significant determinant. Similarly, work which is another proxy for endogenous status has a positive impact on BMI and helps reducing incidence of wasting, but when considered together with time and exogenous status the significance vanishes. Time still remains significant to impact BMI, underweight and wasting. We therefore conclude that mothers' status, measured by time is more important to improve child nutritional status. Finally, our result suggests that the joint effect of time and exogenous variables are particularly crucial to improve child nutrition in households that are affected by a shock.
Keywords: I12; J13; J22; J13; 330; Mothers' time and work; Child nutrition; Food price shock